Deriving the Composite Simpson Rule by Using Bernstein Polynomials for Solving Volterra Integral Equations - Baghdad Science Journal (مجلة بغداد للعلوم, 2014)
In this paper we use Bernstein polynomials for deriving the modified Simpson's 3/8 , and the composite modified Simpson's 3/8 to solve one dimensional linear Volterra integral equations of the second kind , and we find that the solution computed by this procedure is very close to exact solution.